Intelligent Data Mining Techniques for Big Data in Cloud Computing: A Review - Mohammed Hasan, Baraa; Shaker, Fatima (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
The rapid growth of data production across diverse fields created big data as an essential area for both academic study and practical application during recent times. The spread of cloud computing provides businesses with an adaptable infrastructure that enables economical and scalable processing and storage of enormous data collections. Popular use of modern data mining methods requires dealing with major technical obstacles while analyzing massive and complicated information collections. Data mining as an intelligent methodology emerged because it unites artificial intelligence methods with machine learning techniques together with statistical approaches and database operations to resolve these difficulties. In this review paper demonstrates extensive details about Intelligent data mining solutions that operate within cloud infrastructure while handling big data. The paper presents essential details about the basic principles followed by a classification scheme which includes techniques like classification and clustering alongside association rule mining with deep learning methods and their applications for big data needs. This study analyzes data mining system integration models for clouds while it assesses their operational abilities and scalability and makes note of essential difficulties including heterogeneity and real-time processing requirements.